Simulation of implant fitting in the hip bone using maya / Adi Dewiyana Abdul Hadi - Adi Dewiyana, Abdul Hadi (2003)
In today's medical world, attention of researchers of orthopedic surgery now turned toward using 3-D visualization and virtual environment technologies to help surgeons plan for patient specific and complex procedures of operation. For a successful hip surgery, planning is required to decide on type and size of the implant and the reconstruction of the joint geometry. Biomedical analysis and determination of the center of rotation enable the surgeon to choose the theoretically optimal position of the implant. We can plan for the operation by using a computer simulation. Computer simulation provides the conceptual basis to aid the analysis of complex phenomena without building the actual system. From this simulation, surgeon can analyze, create a surgical plan to insert the proposal implant into patient's hip. This proposal project paper will described about the system that will be develop and will explain about all the requirement in developing the project of Simulation of implant fitting in the hip bone. It contains four main chapter, introduction, literature review, methodology, system analysis and system design. Methodology of system development that will be used is the waterfall model. One of the requirements that will be used to develop this project is Maya 4.5 Learning edition. The designing of this system is only a first planning and maybe will change depends on the current situation.